2013
DOI: 10.14417/lp.760
|View full text |Cite
|
Sign up to set email alerts
|

“Experiências em Relações Próximas”, um questionário de avaliação das dimensões básicas dos estilos de vinculação nos adultos: Tradução e validação para a população Portuguesa

Abstract: Resumo Este artigo apresenta o desenvolvimento do questionário "Experiências em Relações Próximas", versão Portuguesa do "Experiences in Close Relationships" (Brennan, Clark, & Shaver, 1998) Universidade de Lisboa, PortugalA correspondência relativa a este artigo deverá ser enviada para: João Manuel Moreira,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
1
5
0
4
Order By: Relevance
“…However, the absence of significant differences in the other domains conflicts with most studies on romantic attachment that have revealed higher avoidance among men than among women (Del Giudice, 2011;Schmitt et al, 2003). This finding is in accordance with the study by Moreira et al (2006) in which no significant gender differences were found in a Portuguese sample of community individuals.…”
Section: Validation Of the Portuguese Version Of The Ecr-rssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the absence of significant differences in the other domains conflicts with most studies on romantic attachment that have revealed higher avoidance among men than among women (Del Giudice, 2011;Schmitt et al, 2003). This finding is in accordance with the study by Moreira et al (2006) in which no significant gender differences were found in a Portuguese sample of community individuals.…”
Section: Validation Of the Portuguese Version Of The Ecr-rssupporting
confidence: 93%
“…In a subsequent meta-analysis, Del Giudice (2011) also found variation in gender differences across cultures, with the largest effect sizes detected in Europe and the Middle East and the smallest in North America. Both studies included the same Portuguese sample (Moreira et al, 2006), in which no significant differences were found between men and women in anxiety and avoidance assessed by the ECR questionnaire. Whether this result reflects a true cultural issue or whether it is a specific result of this particular investigation remains to be clarified.…”
Section: Gender Differences In Attachment Acrossmentioning
confidence: 99%
“…Efetuou-se uma reanálise dos dados do estudo de Afonso (2011), tendo sido selecionados os quatro itens (dos 29 iniciais) com maior saturação, por forma a obter uma versão breve da escala (e.g., "A infidelidade é um modo de vida normal que não tem nada de reprovável"). É pedido aos participantes que indiquem o seu grau de concordância com as frases, numa escala de 1, (Moreira et al, 2006), com os 33 itens (dos 57 originais) mais representativos dos fatores identificados nesta versão. Neste questionário, é pedido aos sujeitos que classifiquem cada um dos itens numa escala de 1, "nada" a 9, "completamente ou extremamente".…”
Section: Instrumentosunclassified
“…O questionário "Experiências em Relações Próximas" (ERP) é a versão portuguesa do "Experiences in Close Relatioships" (Brennan, Clark, & Shaver, 1998), traduzido e adaptado por Moreira et al (2006). Procura avaliar as duas dimensões básicas das diferenças individuais no estilo de vinculação dos adultos: a Evitação e a Preocupação.…”
Section: Instrumentosunclassified
See 1 more Smart Citation